Two-photon fluorescence imaging of sialylated glycans in vivo based on a sialic acid imprinted conjugated polymer nanoprobe. Issue 97 (16th November 2016) - Zhang, Wei; Kang, Junqing; Li, Ping; Liu, Lu; Wang, Hui; Tang, Bo
Abstract : We have designed and synthesized an SA-imprinted conjugated polymer nanoprobe with two-photon fluorescence properties, which exhibits specific recognition ability to the target SA and has been used for monitoring sialylated glycan levels selectively in vivo . Abstract : We have designed and synthesized a sialic acid (SA)-imprinted conjugated polymer nanoprobe with two-photon fluorescence properties, which exhibits specific recognition ability to the target SA and has been used for monitoring sialylated glycan levels selectively in vivo .